Modern views on abattoirs technical installations. - ΑΝΑΣΤΑΣΙΟΥ ΑΝ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author first gives a brief description of the work conditions in the slaughterhouses in Greece. Then he is referring in extense on subjects related to modern abattoirs technical installations and more preciosely the presequintes and the basic terms to erect the buildings, to install the necessary equipment and to valorize the abattoirs by products for medical, industrial and agricultural research. He also gives data for those who are running the abattoirs, for the weat commerce and the cost of using the abattoirs. Finally he is referring to their staff and he is expressing his personnal views for reorganizing on a new rational base the abattoirs in Greece.